Income inequality by ethnic composition of rural households in Vietnam: Evidence from the Oaxaca-blinder decomposition - Son, Tran Minh; Van, Tran Quang; Ha, Nguyen Hong; Huyen, Nguyen Thanh; Dieu, Nguyen Thi Ngoc (Edelweiss Applied Science and Technology, 2024)
This study aims to determine the income gaps of rural households in Vietnam between 02 ethnic groups Kinh and other ethnic groups using the Oaxaca-Blinder (1973) decomposition method. The study is based on the Vietnam Rural Household Resource Access Survey (VARHS) from 2010 to 2018 to identify factors affecting the income gap between 02 Kinh ethnic groups and other ethnic groups. The results of the study show that there is a difference in income between the head of the household who is the Kinh ethnic group and other ethnic groups, the explanation of the Oaxaca-Blinder model shows that the difference in characteristics (age of the head of the household, education level, number of household members, area of productive land, etc) play an important role in explaining the income gap between 02 ethnic groups. The unexplained part reflects disparities due to factors other than characteristics such as discrimination or differences in access to economic opportunities.